Transforming arable and dairy farming systems by adopting anaerobic digestion and recirculating aquaculture systems to address the demand for sustainable profitability, environment and diets - Campos-González, Jorge; Gadanakis, Yiorgos; Sanders, Trystan; Morello, Thiago Fonseca; Mancini, Mattia; Bateman, Ian (My University, 2025)
UK agricultural systems face pressures from environmental targets, policy reform, and market volatility, requiring innovative strategies for resilience and sustainability. This study examines integrating anaerobic digestors (ad, 500 kW) and recirculating aquaculture systems (RaS, 157 m³/unit) in arable and dairy farms. Using a 2022 farm data-based linear programming model, we evaluate the economic viability of producing renewable energy and warm-water prawns alongside traditional outputs. Results show significant profit gains: ad alone boosts net Margins by 24% in arable farms, while combined with RaS can increase margins by up to 56%. For dairy, ad effects are modest (5%), but RaS can improve margins by 70%, often replacing ad due to lower returns. These technologies recycle nutrients from digestate and waste, supporting circular economy goals. ad–RaS synergies maximise energy and heat recovery, with RaS enabling local seafood that reduces import dependence, carbon leakage, and ecological damage from overseas shrimp farming. despite high capital costs, complexity, and energy price sensitivity, findings highlight ad and RaS’s potential for sustainable diversification, align with UK net-zero and biodiversity goals, and improve resource efficiency, lower emissions, and conserve land. We conclude that integrated ad and RaS are viable paths to enhance farm resilience and deliver economic, environmental, and dietary benefits amid agricultural transition.
Keywords: Farm profitability; arm diversification; naerobic digestion; Recirculating Aquaculture Systems; resilient food systems; circular economy